Issues Concerning the Language Standardisation – Theoretical View - Nikolić, Marina (Collection of Papers of the Faculty of Philosophy in Priština, 2020)
Monitoring and evaluating changes in standard languages, especially in Serbian, in the twenty-first century are the focus of this work. In order to determine the situation in the current norm, it is necessary to consider the Serbian language within the context of contemporary European languages. Challenges arising in the process of standardisation of the Serbian language (such as the language democratisation stemming from the democratisation of society, modernisation, rapid establishment of a gender-sensitive language and insisting on its use, social network terms, etc.), but likewise the needs that such a language should cover, are common with those in other European languages.The principal aim is to shed light on changes in the traditional Serbian language generating a parallel norm, which we refer to as ʻneo-standardʼ, and whose formation is predominantly influenced by the media. The second objective is to exactly and thoroughly determine the reasons for the emergence of neo-standard, which, as previous research have shown, are common in all European languages.
Keywords: standard language; neo-standard; media; Serbian language